The Effectiveness of Project-Based Learning in Improving Students' Speaking Skills in EFL Classrooms - Putra, Syahyar Ridhana (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the effectiveness of Project-Based Learning (PBL) in improving students' speaking skills in learning English as a Foreign Language (EFL) among eleventh-grade students at a public senior high school in Cirebon, Indonesia. The study was motivated by the low level of students' oral communication skills, limited opportunities to practice speaking, lack of confidence when expressing ideas in English, and the dominance of teacher-centered learning approaches in the classroom. To address these issues, PBL was implemented as an instructional strategy that encourages students to engage in meaningful communication through collaborative projects and real-world tasks. This research employed a quasi-experimental method using a pre-test and post-test control group design. The participants were divided into an experimental group, which received instruction through PBL, and a control group, which was taught using conventional teaching methods. Data were collected through speaking tests, classroom observations, and student questionnaires. The speaking assessments focused on fluency, accuracy, pronunciation, and interaction. The findings revealed that students in the experimental group showed significantly greater improvement in their speaking performance compared to those in the control group, particularly in fluency and interaction. Furthermore, students reported higher levels of motivation, engagement, and self-confidence in speaking English. Therefore, it can be concluded that PBL is an effective approach for enhancing EFL students' speaking skills and communicative competence through active, collaborative, and contextual learning experiences.